2007
DOI: 10.4064/ba55-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Fibonacci Numbers with the Lehmer Property

Abstract: Summary. We show that if m > 1 is a Fibonacci number such that φ(m) | m − 1, where φ is the Euler function, then m is prime.Let φ(n) be the Euler function of the positive integer n. Clearly, φ(n) = n − 1 if n is a prime. Lehmer [9] (see also B37 in [7]) conjectured that if φ(n) | n−1, then n is prime. To this day, no counterexample to this conjecture (and no proof of it either) has been found. Let us say that n has the Lehmer property if n is composite and φ(n) | n − 1. Thus, Lehmer's conjecture is that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Many results concerning this problem can be found in the litterature (see [1], [9]). Not succeeding in proving that there are no numbers with the Lehmer property, some researchers concentrated on proving that there are no numbers with the Lehmer property in certain interesting subsequences of positive integers like in the Fibonacci sequence {F n } n≥0 and its companion sequence {L n } n≥0 (see [5] and [8]). In [4] and [6], it was shown that there are no numbers with the Lehmer property in the sequence of Cullen numbers {C n } n≥1 of general term C n = n2 n + 1, and in some appropriate generalization of the sequence of Cullen numbers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Many results concerning this problem can be found in the litterature (see [1], [9]). Not succeeding in proving that there are no numbers with the Lehmer property, some researchers concentrated on proving that there are no numbers with the Lehmer property in certain interesting subsequences of positive integers like in the Fibonacci sequence {F n } n≥0 and its companion sequence {L n } n≥0 (see [5] and [8]). In [4] and [6], it was shown that there are no numbers with the Lehmer property in the sequence of Cullen numbers {C n } n≥1 of general term C n = n2 n + 1, and in some appropriate generalization of the sequence of Cullen numbers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…At present no Lehmer number is known. Recently it was proved that certain sequences of integers such as the Fibonacci sequence do not contain a Lehmer number (see, for example, [1], [6]). …”
Section: Introductionmentioning
confidence: 99%
“…In [5], it was shown that there is no Lehmer number in the Fibonacci sequence. We will refer to such numbers simply as repunits without mentioning the dependence on g. It is not known whether, given g, there are infinitely many repunit primes.…”
Section: Introductionmentioning
confidence: 99%